Surfactant-free one-pot synthesis of Au-TiO2 core-shell nanostars by inter-cation redox reaction for photoelectrochemical water splitting. (15th January 2022) - Cho, Sanghyuk; Yim, Gyeonghye; Park, Jung Tae; Jang, Hongje
Graphical abstract: Highlights: The nanostar core structures are synthesized via a novel ICR reaction. TiO2 are deposited on the nanostar, imparting control over tip-capped to core-shell. The Au-TiO2 nanostar structure is employed as a photoanode in PEC applications. The Au-TiO2 nanostars enhanced the PEC performance due to the LSPR effects. This synthetic protocol enables rapid and reproducible nanostructure fabrication. Abstract: We used a novel inter-cation redox reaction between two metal cations with different redox potentials to synthesize nanostar structures without the addition of toxic surfactants, surface-adsorbing polymers, or additives with intrinsic reducing power. Along a multistage reaction route, the nanostars were fabricated via a shift in mechanism from kinetic to thermodynamic control. Next, semiconducting TiO2 shells were deposited on the nanostar surface, with controlled formation of tip-capped or closed core–shell structures depending on the reaction conditions. The Au-TiO2 nanostar structure was subsequently applied in a photoanode for photoelectrochemical applications. Specifically, the photoanode was prepared by depositing the nanostars onto hydrothermally grown TiO2 nanorods on fluorine-doped tin oxide. The deposition of Au-TiO2 nanostars enhanced the photoelectrochemical performance of the water-splitting device owing to the localized surface plasmon resonance effect in the Au nanoparticles, which can be attributed to an enhanced efficiency of incident photon-to-electron conversion. Compared to the pristine TiO2 nanorods, the Au-TiO2 nanostar on TiO2 nanorods exhibited a 33% increase in photocurrent density at 1.23 V vs. the reversible hydrogen electrode under AM 1.5 G simulated sunlight irradiation (100 mW cm −2 ). This minimal synthetic protocol enables the rapid and reproducible fabrication of nanostructures. It also provides new possibilities for nanostructure synthesis via spontaneous complex formation of independent end-products and applications in the photoelectrochemical water splitting system.